Water QualityOf SibakurRodfor Nila Fish Keramba Systems in the Deep Sub TarokVillages LatangSijunjungDistrict - Gamiarsih, Elva; Edial, Helfia; Juita, Erna (STKIP PGRI Sumbar, 2013)
Water Sibakur rod located in deep sub Latang Tarok villages are common water resource that has an important role for the people living around. sibakur stem water use by local people covering different aspects of life. of them as a place of cage fishfarming, fishing area, water the fields, and household activities. purpose of fish farming is to produce fish in larger quantities than the natural life.This study aimed to obtain information, data, analyzes, discusses and discloses: (1) physical condition sibakur system water for nila fish cage systems which include temperature, color, and turbidity (2) water chemistry conditions Sibakurrod for nila fish farming cage systems which included pH, dissolved oxygen (DO), carbondioxide(CO2), phosphates (PO4) and ammonia (NH3). Type of research is descriptive research. this study to determine the physical and chemical parameters of water were used as SibakurBatang fish farming cage Systems. This study compared the results of the analysis are obtained directly from the field and laboratory with water quality standards for aquaculture. The samples tested were in the region of the upstream, midstream, and downstream water Sibakur Trunk. The results on the physical and chemical parameters tabulated and analyzed descriptively. Results of the study are as follows: (1) Water Quality Rods Sibakur for nilafishfarming cagesystems in physics, namely the temperature Stem water Sibakur eligible because the water temperature of all test samples are still within the range of 25-290C. Color and water requirements. (2) The water quality for fish rod Sikabur chemically meet requirements that included pH, Carbohydrate (CO2) to meet the requirements of the upstream and downstream while the center does not meet the requirements, Dissolved oxygen (DO), phosphate (PO4), and Ammonia ( NH3) does not meet the requirements due to exceeding quality standards for tilapia farming.